Resuscitating roots restoring and documenting oral culture in Mozambique using architecture & mnemonics - Fragoso, Raguel (My University, 2019)
Mozambique’s culture is predominantly an oral culture. This means that it is a culture that perceives, receives and gives through hearing and speaking. Cultural values and norms are not written down or recorded in any way but are passed on from generation to generation through storytelling and verbal teachings, using the various local dialects. Most of the people who comprehend and use local dialects belong to older generations. The passing on of cultural heritage to younger generations has been a challenge. As a result, there has been a neglect and loss of culture and traditions especially in younger generations. Mozambique has a lack of cultural activities which cater for a diverse public and have an educational component to it. This research studied how Architecture can promote the process of remembrance of an oral and sensorial culture through sensory experiences and mnemonics in order to restore, document and transfer it to future generations. This research was an informant for the design development of a Cultural Centre which promotes the process of restoration and remembrance of a forgotten culture as well as the process of learning languages. The material used conduct this research was gathered through readings, interviews with anonymous participants, personal observations and personal knowledge obtained during the years that I lived in Mozambique. The Cultural Centre is formed by four components: the performance space, the interactive museum, the learning areas and the research spaces. All the cultural performances are recorded and then taken into the interactive museum as an exhibition as well as into the research areas where they are studied and documented. From the research area it is then taken into the learning spaces to be taught and passed on. These learning areas also cater for cultural
School of Architecture & Planning University of the Witwatersrand Johannesburg, South Africa February 2019